Pendampingan Guru SD dalam Pembelajaran Matematika Inovatif Berbasis Kecerdasan Emosional dan Teknologi Interaktif: Pengabdian - Nurwahidin, Muhammad; Riswandi; Apryani, Dina; Adina Pratama, Maya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) aims to enhance teachers’ capacity in implementing innovative mathematics learning based on emotional intelligence and interactive technology at SD Negeri 2 Wonodadi, Pringsewu Regency. The main challenges faced by the partner school include the limited use of digital media and the teachers’ difficulties in managing students’ emotions during mathematics lessons. The program adopted a reflective mentoring approach consisting of three main stages: (1) orientation and basic training, (2) reflective discussion and teacher community strengthening, and (3) evaluation through post-tests, teacher response questionnaires, and collective reflection sessions. The results reveal significant improvements in teachers’ ability to use Wayground as an effective interactive learning platform and in their emotional regulation skills within classroom interactions. Teachers successfully integrated technology and empathy into mathematics teaching, resulting in increased student motivation, engagement, and confidence. Moreover, the program fostered the establishment of a teacher learning community focused on continuous reflection and collaboration, marking a form of social transformation within the school.